ChemInform Abstract: Rhodium‐Catalyzed Annulation Between 2‐Arylimidazo[1, 2‐a]pyridines and Alkynes Leading to Pyrido[1, 2‐a]benzimidazole Derivatives. Issue 37 (September 2015) - Peng, Haibo; Yu, Jin‐Tao; Jiang, Yan; Wang, Lei; Cheng, Jiang
Abstract The method tolerates chloro, bromo, cyano, and methoxycarbonyl groups.